Ericto, a feiticeira: a magia nas tramas da tradução castilhiana (Pharsalia, VI, 438-569) - Moraes, Débora Cristina de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The translation studies have raised new research in several areas that include translation as reception and criticism. If in other times this work was seen simply as parafrástica interpretation of the original text , this time other requirements are imposed . The role of the translator and an inherent aggregate theory to their work are checked in the final product of the translated work - the target text . The theoretical elected by us to base a significant part of the work is the French Antoine Berman , with two important works for the modern theory of translation, Translation and the letter or a shelter for the far-way and the chapter The manifestation of translation, which is inserted into The Experience of the Foreign . Through these readings, attempts to glimpse the theoretical practice of a fruitful translator of the nineteenth century: José Feliciano de Castilho . Among his notes to his version of Amores of Ovid (called Grinalda Ovidiana) , we chose an excerpt from Pharsalia of Lucan for analysis and reflection of translational do in our literature at an important time of their formation

Os estudos de tradução têm, na atualidade, suscitado novas pesquisas nas diversas áreas que englobam a tradução como recepção e crítica. Se em outros tempos este trabalho era visto simplesmente como interpretação parafrástica do texto ―original‖, neste momento outras exigências se impõem. O papel do tradutor e uma inerente teoria agregada ao seu trabalho são verificados no produto final da obra traduzida - o texto de chegada. O teórico eleito por nós para basear uma significativa parte do trabalho é o francês Antoine Berman, com duas importantes obras para a teoria moderna da tradução, A tradução e a letra ou o albergue do longínquo e o capítulo ―A tradução em manifesto‖, que está inserido em A prova do estrangeiro. Através dessas leituras, tenta-se vislumbrar a praxe teórica de um tradutor profícuo do século XIX: José Feliciano de Castilho. Dentre suas notas à versão de Os amores, de Ovídio (denominada Grinalda Ovidiana), elegemos um excerto da Farsália de Lucano para análise e reflexão do fazer tradutório em nossa literatura em uma importante época de sua formação
Keywords: Noronha, José Feliciano de Castilho Barreto e; Traduções; Literatura latina; Translations